Quality characteristics and shelf-life of meat of quail birds-fed diets supplemented with grape pomace - SABOW, AZAD; ABDULLA, NAZIM; MUSTAFA, HOZAN; ABUBAKAR, AHMED (The Indian Journal of Animal Sciences, 2022)
This investigation aims to determine the effect of grape pomace supplementation on quail meat’s quality and shelf life. Growing 121-day-old quail males were separated into groups of 30 birds each (3 replicates of 10 birds each). For 42 days, the quails were fed a diet enriched with 0, 2.5, 5, or 10 g/kg of grape pomace (control group and experimental groups). After the feeding session, ten quails were chosen randomly and slaughtered humanely to test the meat quality. Except for redness, which showed a lower value for experimental groups compared to the control group, neither the physicochemical characteristics nor the eating quality of breast meat varied significantly across treatments. The experimental groups also produced alterations in the fatty acid profile, with an increase in polyunsaturated fatty acids mainly due to an increase in linoleic acid concentration. The addition of grape pomace reduced lipid oxidation in meat at 1 and 5 days post-mortem. On post-mortem day 5, the control group meat had more bacteria than the experimental group meat. Overall, supplementation with grape pomace significantly improved the fatty acid profile and showed the capacity to extend shelf life.